THU0767-HPR Advanced practice musculoskeletal physiotherapy services: a national evaluation. (15th June 2017) - Fennelly, O; Blake, C; Fitzgerald, O; Breen, R; Brennan, A; Ashton, J; Cunningham, C; ,
Abstract : Background: Patients with musculoskeletal (MSK) disorders may remain on lengthy hospital outpatient waiting lists to be reviewed by a consultant doctor, although medical or surgical intervention may not be required (1, 2). In 2012, a waiting list initiative saw the introduction of Advanced Practice Physiotherapists (APPs) across 16 hospitals in Ireland. APPs triage and manage patients awaiting a consultant doctor appointment, who are deemed non-urgent or unlikely to require surgery on screening of referral letters. APP scope of practice generally involves some traditionally medical-controlled acts such as: administering injections, ordering investigations/imaging, surgical listing and onward referral to hospital specialities; and depending on consultant doctor availability, their input may be sought on clinical decisions if required. Objectives: Profile the national APP patient caseload Establish the clinical outcomes of APP consultations Methods: A national database was established with all APPs (n=22) submitting patient data for 2014. These data were analysed using descriptive statistics. Results: Data showed that APPs assessed 13, 981 new patients, who presented most commonly with MSK disorders of the knee (n=3, 096), lumbar spine (n=2, 926) and shoulder (n=1, 945) (Fig. 1) and the median wait time was 167 days (IQR 91–316). Including an additional 2, 596 return appointments, the most common clinical outcomes were physiotherapy and/or clinical investigations (Table 1), and clinical decisions were made independently by the APP in 77% (n=11, 728) of recorded cases (n=15, 189). Conclusions: APP services provide a more efficient MSK clinical pathway and reduce demands on the Consultant Doctor services. Collection of National Data enables ongoing service evaluation and monitoring of key performance indicators. References: Wood, L., Hendrick, P., Boszczyk, B. & Dunstan, E. 2016. A review of the surgical conversion rate and independent management of spinal extended scope practitioners in a secondary care setting. Ann R Coll Surg Engl, 1–5. Desmeules, F., Toliopoulos, P., Roy, J. S., Woodhouse, L.J., Lacelle, M., Leroux, M., Girard, S., Feldman, D.E. & Fernandes, J. C. 2013. Validation of an advanced practice physiotherapy model of care in an orthopaedic outpatient clinic. BMC Musculoskelet Disorders, 14, 162. Acknowledgements: I would like to thank the National Clinical Programmes and Health Service Executive for their funding and support of this project. Disclosure of Interest: None declared